Signal propagation in aquaculture environment for wireless sensor network applications - Azizi, Harun; Ndzi, David Lorater; M. F., Ramli; Ali Yeon, Md Shakaff, Prof. Dr. (EMW Publishing, 2013)
Link to publisher's homepage at